Exploring the Feasibility of Smartphone Cameras for 3d Modelling of Bite Patterns in Forensic Dental Identification - Arofi Kurniawan; Janice Hamdani; An'nisaa Chusida; Haryono Utomo; Beta Novia Rizky; Beshlina Fitri Widayanti Roosyanto Prakoeswa; Azra Rahma Yuniar; Rodrigo Salazar-Gamarra; Aspalilah Alias; Mohd Yusmiaidil Putera Mohd Yusof; Anand Marya (Elsevier, 2024)
Indexed by WOS/Scopus